Pengaturan Mini Baner, Brosur, Dan Spanduk Sebagai Media Promosi - Aritya Saputri; Aditya Wijaya (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
The increasing demand for medicines, especially in Indonesia, is a promising business opportunity in terms of sales. So that many companies set up this business to meet consumer needs. This makes competition among entrepreneurs to meet the needs of the company and expand the marketing area in order to maintain the viability of the company. The company will also try to disseminate information so that old customers make purchases. As for one way that can be done by the company to face the competition is to do promotions. Promotion is a strategy that plays an important role for the continuity of the company. The company will work with designers to create promotional media as a visual communication tool. This requires designers to be more creative in making promotional media that the company wants.